2018
DOI: 10.1039/c8ce01450g
|View full text |Cite
|
Sign up to set email alerts
|

A study of GaN nucleation and coalescence in the initial growth stages on nanoscale patterned sapphire substrates via MOCVD

Abstract: A study of GaN nucleation and coalescence behaviors in the initial growth stages on nanoscale patterned sapphire substrates (NPSS) is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 42 publications
1
28
0
Order By: Relevance
“…Both the values were red-shifted from the E 2 (high) wavenumber from a standard free-standing bulk GaN (567.5 cm −1 ), proving that the GaN epilayers in the reference and sample C were under tensile stress [ 26 ]. Shifts of the E 2 (high) phonon peak are related to the relaxation of residual strain; it can be calculated using the following equation [ 27 ]: where ω γ and ω 0 represent the Raman wavenumbers of the E 2 (high) phonon peak of sample C and reference sample, respectively. A proportionality factor K γ (4.2 cm −1 GPa −1 ) originates from hexagonal GaN [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Both the values were red-shifted from the E 2 (high) wavenumber from a standard free-standing bulk GaN (567.5 cm −1 ), proving that the GaN epilayers in the reference and sample C were under tensile stress [ 26 ]. Shifts of the E 2 (high) phonon peak are related to the relaxation of residual strain; it can be calculated using the following equation [ 27 ]: where ω γ and ω 0 represent the Raman wavenumbers of the E 2 (high) phonon peak of sample C and reference sample, respectively. A proportionality factor K γ (4.2 cm −1 GPa −1 ) originates from hexagonal GaN [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…The cross-sectional SEM images of GaN films on 10, 25, and 40 nm sputtered AlON/PSS templates were taken from the [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ] direction, presented in Figure 5 . From the cross-sectional SEM image of the GaN film on the 10 nm sputtered AlON/PSS template, we could clearly observe that GaN could not coalesce well.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, with the appropriate nucleation layer (NL), most GaN grows in the flat regions between cones, though the flat region is a rather small proportion of the whole substrate, no matter what the geometry of the pattern is [ 10 , 11 , 12 ]. However, some GaN would still form small GaN crystals on the cone sidewalls, which may have negative influences on GaN growth [ 13 , 14 ]. In our previous work, we confirmed that small GaN crystals would generate dislocations [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of GaN NL during annealing is to provide nucleation islands (NIs) for the GaN crystallites and to promote the lateral growth of the film. The thermal annealing process was found to have an important effect on the properties of the subsequent GaN film [5]. After the anealing of NL, the GaN NL will transform to three-dimensional (3D) NIs.…”
Section: Introductionmentioning
confidence: 99%